The Limits of Propaganda: Evidence from Chavez's Venezuela. Issue 2 (7th April 2018) - Knight, Brian; Tribin, Ana
Abstract: We investigate viewer responses to ideological changes in television programming induced by cadenas, unannounced government propaganda in Venezuela. The drop-off in ratings during cadenas is concentrated among viewers of news programming on opposition channels, relative to progovernment channels. Also, the drop-off in ratings for moderate channels takes an intermediate value. The drop-off is stronger for viewers with access to cable channels, which do not air cadenas and experience an increase in viewership during cadenas. Structural estimation of our model allows us to quantify the degree to which opposition viewers limit their exposure to and ultimately the influence of propaganda via tuning out.